PENGARUH TINGKAT PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT KARYA SAWITINDO MAS (KSM) - Subandrio Subandrio; Asminawati Asminawati (UM. Bengkulu, 2022)
This research was conducted at PT KSM (Karya Sawitindo Mas) Tanjung Alai Village, Lubuk Pinang District, Mukomuko Regency, Bengkulu Province. This research is a quantitative research in which the researcher proves by using numbers on a number of populations and samples that are considered worthy of research. This method is used to examine statistical data in order to be able to test a hypothesis obtained by the research field. Based on the results of hypothesis testing using the t test, the Education Level variable has a positive and significant effect on employee performance, this can be seen from the results of the t test which states the t value of sig < = 0.000 < 0.05). The results of t-test of work experience variable also show a positive and significant influence result on employee performance, this can be seen in the value of t-test result which states that t sig <Î± = 0.000 < 0.05). The results of the analysis above show that the level of education and work experience has an influence on employee performance, this can be seen in the f test which shows the value of t sig <Î± = 0.000 < 0.050), so it can be concluded that H_3 is accepted, meaning that simultaneously the variable of education level and work experience has an influence on employee performance at PT KSM (Karya Sawit Indomas) employees.â€ƒÂ Keywords: Education Level, Work Experience and Employee Performance.